ANALISIS SWOT DAN ASPEK KEUANGAN STUDI KELAYAKAN INVESTASI PENGEMBANGAN RUMAH SAKIT UMUM WONOLANGAN PROBOLINGGO - Wilujeng, Titin Amrih; Riyadi, Slamet; Ridwan, Mohammamad Sihab (JEB17 : Jurnal Ekonomi dan Bisnis, 2019)
The purpose of this research is to analyze and inperprete of feasibility and unworthiness of development investment Wonolangan Hospital.This research use methode kualitative descriptive with instrumen observasion,interview and dokumentation. There are two instrumen that are. 1.SWOT analysis Wonolangan Hospita Probolinggo City and Feasibility study investmentÂ  Wonolangan Hospital Probolinggo City The research subject is Wonolangan Hospital Probolinggo with Head of the Hospital,Director of Operation,Commercial director and Head of Marketing,Services dan Bussiness Development Division as informans.The result are Pay back Periode receach after 10,95 years, NPV positive as big as 37.457.976 with discount factor 10% and IRR â€“ 73.665.872.Conclusion from the result investment is not feasible to develop.